2002
DOI: 10.1007/s00259-001-0745-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rhTSH on [18F]fluorodeoxyglucose uptake by differentiated thyroid carcinoma

Abstract: The influence of serum TSH levels on fluorine-18 fluorodeoxyglucose (FDG) uptake by recurrences or metastases of differentiated thyroid carcinomas has not yet been clarified. The aim of this study was to ascertain whether the administration of recombinant human thyrotropin (rhTSH) stimulates FDG uptake by such lesions. In this prospective study, 30 patients with positive or equivocal thyroglobulin (Tg) levels and negative or equivocal iodine-131 and/or morphological imaging results (ultrasound, MRI, CT) underw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
54
0
10

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(64 citation statements)
references
References 17 publications
0
54
0
10
Order By: Relevance
“…Do TSH stimulations done under THW or rhTSH before PET increase the detection of tumor sites? PET imaging done under TSH stimulation reveals more lesions in a greater number of patients with a significantly increased tumor-to-background ratio than paired scans done during TSH suppressive therapy (THS) (7)(8)(9). However, no significant scan outcomes were found in other studies (10,11).…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…Do TSH stimulations done under THW or rhTSH before PET increase the detection of tumor sites? PET imaging done under TSH stimulation reveals more lesions in a greater number of patients with a significantly increased tumor-to-background ratio than paired scans done during TSH suppressive therapy (THS) (7)(8)(9). However, no significant scan outcomes were found in other studies (10,11).…”
Section: Introductionmentioning
confidence: 74%
“…Of these references, we excluded 70 citations based on their title, abstract, or both because they were not relevant to the question under study. After reading the full text of 13 potentially relevant publications, six were excluded because they were retrospective studies without controls and did not fulfill the inclusion criteria (7,(15)(16)(17)(18)(19). Seven prospective controlled clinical trials with 168 patients were included (8,9,11,(20)(21)(22)(23) …”
Section: Results Of the Searchmentioning
confidence: 99%
“…Petrich et al found that the number of positive scans, as well as the number of lesions and standardized uptake values (SUV), increased with the use of rhTSH stimulation (28). In contrast, Leboulleux et al found that the number of positive scans did not increase, but the number of identified lesions did increase after stimulation with rhTSH; the increased number of lesions changed management in about 6% of cases (29).…”
Section: Discussionmentioning
confidence: 94%
“…O TSH estimula o sistema de transporte de glicose na membrana celular aumentando o grau de captação de FDG-18 F no tumor (13,14). No presente estudo, a relação entre o nível de TSH e o resultado da PET-CT não foi avaliado, pois 22 dos 25 pacientes realizaram a pesquisa sob estímulo do TSH.…”
Section: Discussionunclassified